National Health Insurance implications for rehabilitation professionals and service delivery - H. Myezwa; M. van Niekerk (South African Journal of Physiotherapy, 2013)
This paper reviews the National Health Insurance (NHI) in view of what is proposed and authors suggest how it may impact on the rehabilitation sector namely occupational therapy, physiotherapy, speech and language therapy and audiology. A review of the basic description of the NHI and the different elements is presented. Particular attention is paid to how much interface and mention is made of rehabilitation. The current status of rehabilitation service provision and its response to the needs of the population, in particular the burden of disease and the related finance models are discussed. Suggestions are presented for the way forward to ensure rehabilitation professionals and services rendered are not caught flat footed.